How the Use of a Patient-Accessible Health Record Contributes to Patient-Centered Care: Scoping Review - Benjamins, Janine; Haveman-Nies, Annemien; Gunnink, Marian; Goudkuil, Annemieke; de Vet, Emely (JMIR Publications, 2021)
BackgroundWorldwide, patient-centered care is becoming a widely used concept in medical practice, getting more and more attention because of its proven ability to improve quality of care and reduce costs. Although several studies show that patient-accessible electronic health records (PAEHRs) influence certain aspects of patient-centered care, the possible contribution of PAEHR implementation to patient-centered care as a comprehensive concept has not, to our knowledge, been structurally evaluated to date. ObjectiveThe objective of this study is to review whether and how the use of PAEHRs contributes to patient-centered care both in general and among specific population groups. MethodsWe followed PRISMA Extension for Scoping Reviews reporting guidelines. We identified literature in 5 databases, using the terms "patient-accessible medical records," "patient experiences," and "professional experiences" as key concepts. A total of 49 articles were included and analyzed with a charting code list containing 10 elements of patient-centered care. ResultsStudies were diverse in design, country of origin, functionalities of the investigated PAEHR, and target population. Participants in all studies were adults. Most studies reported positive influence of PAEHR use on patient-centered care; patient accessible health records were appreciated for their opportunity to empower patients, inform patients about their health, and involve patients in their own care. There were mixed results for the extent to which PAEHRs affected the relation between patients and clinicians. Professionals and patients in mental health care held opposing views concerning the impact of transparency, where professionals appeared more worried about potential negative impact of PAEHRs on the patient-clinician relationship. Their worries seemed to be influenced by a reluctant attitude toward patient-centered care. Disadvantaged groups appeared to have less access to and make less use of patient-accessible records than the average population but experienced more benefits than the average population when they actually used PAEHRs. ConclusionsThe review indicates that PAEHRs bear the potential to positively contribute to patient-centered care. However, concerns from professionals about the impact of transparency on the patient-clinician relationship as well as the importance of a patient-centered attitude need to be addressed. Potentially significant benefits for disadvantaged groups will be achieved only through easily accessible and user-friendly PAEHRs.